2021
DOI: 10.33448/rsd-v10i15.21813
|View full text |Cite
|
Sign up to set email alerts
|

Biossegurança no ambiente odontológico e prevalência de COVID-19 em Cirurgiões-Dentistas do estado da Paraíba

Abstract: O objetivo do presente trabalho foi avaliar a prevalência de cirurgiões-dentistas do estado da Paraíba acometidos pelo novo Coronavírus e os seus conhecimentos sobre as normas de biossegurança para controle de disseminação do vírus no ambiente odontológico. O estudo foi do tipo quantitativo, analítico e descritivo, desenvolvido por meio da aplicação de um questionário eletrônico destinado aos cirurgiões-dentistas do estado da Paraíba. Os dados foram processados com o auxílio do programa estatístico SPSS, versã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…This study confirmed, as other studies have done before, that the pandemic triggered a great concern and interest among dental personnel to learn about the risk of COVID 19 and how to deal with it, and as a consequence, most professionals incorporated the use of new equipment, clothing and supplies into their practice. [2][3][4]9], What this study was able to document, however, is that the adoption of these biosecurity practices, more than the protocols issued by formal institutions, was due to the emotion of fear and uncertainty that invaded the professionals, those who acted in recognition of and prioritised their own vulnerability to SARS-COV2, since the perception of risk was identified as being based, as has been documented in other studies, on the fear of becoming infected or bringing the disease to their relatives [16]. This is to be expected since, as Susan Cutter says, although «risks are always present, they become hazards only when humans or the environment come into contact with them», Under this premise, elaborating a perception of risk in general and in the first place demands that we assume ourselves to be vulnerable in relation to what is threatening, because it is in contact with it that we have the opportunity to subjectivise risk, to stop contemplating it as something abstract and to assume it as an experience that acquires a sense of ominousness, that occurs when experiences that have become commonplace suddenly involve conditions over which we perceive a sense of lack of control or affect our familiarity with those situations [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study confirmed, as other studies have done before, that the pandemic triggered a great concern and interest among dental personnel to learn about the risk of COVID 19 and how to deal with it, and as a consequence, most professionals incorporated the use of new equipment, clothing and supplies into their practice. [2][3][4]9], What this study was able to document, however, is that the adoption of these biosecurity practices, more than the protocols issued by formal institutions, was due to the emotion of fear and uncertainty that invaded the professionals, those who acted in recognition of and prioritised their own vulnerability to SARS-COV2, since the perception of risk was identified as being based, as has been documented in other studies, on the fear of becoming infected or bringing the disease to their relatives [16]. This is to be expected since, as Susan Cutter says, although «risks are always present, they become hazards only when humans or the environment come into contact with them», Under this premise, elaborating a perception of risk in general and in the first place demands that we assume ourselves to be vulnerable in relation to what is threatening, because it is in contact with it that we have the opportunity to subjectivise risk, to stop contemplating it as something abstract and to assume it as an experience that acquires a sense of ominousness, that occurs when experiences that have become commonplace suddenly involve conditions over which we perceive a sense of lack of control or affect our familiarity with those situations [17].…”
Section: Discussionmentioning
confidence: 99%
“…In the perception of risk that the professionals constructed, it can be observed that within the framework of the emotion of fear and uncertainty, they prioritised above all their personal safety, as Renn mentions [18] individuals in a state of risk become more individualistic and hierarchical, with a pessimistic outlook and increased vulnerability to risks. Professional risk should cease to be seen as a fatality and should be assumed as an act of responsibility, but for this to happen, more must be done than just including microbiology content in the subjects; reflective processes must be encouraged in real practice, situations that the informants say they have not experienced, and which explains why even though other authors have reported that the level of knowledge about cross-infection is acceptable, this does not translate into safe interventions in practice [5][6][7][8][9]. In the light of the above, we have identified that there is a tendency to normalise risk, and even to devalue the risk when it comes to cross-infection in the user population, a situation that is relevant because it shows how, while recognising and even overestimating one's own risk, The user's perception of risk is accepted on a daily basis, as Douglas' contributions show, because the perception of risk also emerges from the processes of interaction that prevail in relationships [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With social isolation, however, the population as a whole began to make more use of these tools 23 model in both outcomes, in which younger professionals felt less prepared and safe, and more anxious and concerned about working during the pandemic. In Turkey, recent dentistry graduates seemed to be the most affected during the pandemic 24 and a study in Paraíba State in Brazil showed greater confidence in working during the pandemic among older dentists, which can be explained by their being longer in practice and more stably established in the profession 25 .…”
Section: Discussionmentioning
confidence: 99%
“…A idade foi o único fator individual de influência mantido no modelo teórico dentro dos dois desfechos, com os profissionais mais jovens se sentindo menos preparados e seguros, e mais ansiosos e preocupados, para trabalhar durante a pandemia. Na Turquia, cirurgiões-dentistas recém-formados parecem ser os mais afetados durante a pandemia 24 , e no estado da Paraíba, estudo mostrou maior segurança em atuar durante a pandemia entre os cirurgiões-dentistas mais idosos ou com maior idade, o que pode se justificar pelo maior tempo no mercado de trabalho e maior estabilidade na profissão 25 .…”
Section: Gênerounclassified